Class size as a determinant factor in dietary changes in nursing students. - Fernandez Alonso, Julia; Lamas-Mendoza, Maria del Mar; Caballero-Sanchez, Silvia; San Juan-Escudero, Ainara; Fernández-Aedo, Irrintzi; Gravina-Alfonso, Leyre (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: While nursing students receive foundational education in biochemistry and nutrition during their first year of studies, the influence of nutrition education at the university level on their dietary behavior, particularly considering class size, remains unclear. Aim: The aim of this study is to assess the impact of a nutrition course on dietary changes among undergraduate nursing students, taking into account the size of the class group. Methodology: A pre-post quasi-experimental study with a within-subject design was conducted, measuring the baseline period (T0-T1) and intervention period (T1-T2). The educational intervention focused on providing basic nutritional knowledge about nutrients, balanced diets and the Mediterranean Diet within a Faculty of Medicine and Nursing. Participants included first-year undergraduate nursing students, divided into three groups based on class size: large group (n = 101), medium group (n = 70) and small group (n = 22). The frequency of recommended food group consumption for main, daily, weekly and occasional meals, as well as adherence to the Mediterranean Diet was analyzed. Findings: Only the small class group demonstrated a significant improvement in dietary quality following the educational intervention (p < 0.05), with increased consumption of fruits (p < 0.05), nuts (p < 0.001), and oily fish (p < 0.05). Discussion: Choosing the best teaching strategy can be crucial in getting nursing students to put healthy dietary knowledge into practice to improve their eating habits. Conclusions: The findings suggest that enhancing students’ personal dietary habits can contribute to the improvement of their nutrition counseling skills.